FOXP3 expression in papillary thyroid carcinoma with and without Hashimoto's thyroiditis - Murilo Pedreira Neves Junior; Edgar Marcelino de Carvalho Filho; Marcos Pedro Guedes Camandaroba; Milena Brachmans Mascarenhas; Thaizza Cavalcante Correia; Yuri Costa Sarno Neves (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: The forkhead box P3 (FOXP3) plays a role in cell development and control. In the presence of abnormal FOXP3 expression, tumor cells may evade the immunosurveillance of lymphoid cells, the first step for the maintenance of cancer cells in the thyroid tissue. OBJECTIVE: To identify the presence of FOXP3 in papillary thyroid carcinoma (PTC) with and without Hashimoto's Thyroiditis (HT). METHODS: We conducted a series study of cases collected from 2000 to 2008, when 1,438 thyroidectomies were performed. We selected those diagnosed with PTC, comprising 466 cases. 30 patients were randomly selected for purposes of immunohistochemistry with antibodies against FOXP3. RESULT: FOXP3 revealed high positivity for PTC and positive immunostaining was present in 21 (72.4%) from all analyzed cases. There was no difference regarding coexistent HT or not. DISCUSSION AND CONCLUSION: In the present study, it was evidenced that the focal or diffuse FOXP3 expression was commonly observed in neoplastic cells from PTC, hence indicating that the assessment of this molecule expression in suspected cases of thyroid cancer may contribute to its diagnosis.